Project and construction of a bioreactor for reactions catalyzed by baker's yeast (Saccharomyces cerevisiae). - Pereira, R. D. (Soc Brasileira Quimica, 1997)
A model for the construction of a simple and cheap apparatus to be used as bioreactor for reactions catalyzed by baker's yeast (Saccharomyces cerevisiae) is described, The bioconversion and separation of cells from products and residual substrates are obtained at the same time, The reactions carried out in this type of reactor are faster than those catalyzed by immobilized cells, Yeast cells can be cultivated in this bioreactor operating with cell recycling at appropriated conditions using glucose and other nutrients.
Keywords: baker's yeast; Saccharomyces cerevisiae; reactor; immobilized cells; asymmetric synthesis